Evaluación del crecimiento de neonatos de Crocodylus acutus (Crocodilia: Crocodylidae) en cautiverio - Piedra C., Lilliana (1996)
Two diets, two feeding frequencies, and two densities were tested in 64 captive crocodile Crocodylus acutus juveniles. The higher feeding frequency (five times per week) and the red meat-based diet produced a higher weight